Independensi, Pengalaman Kerja Auditor, dan Kualitas Audit Dengan Skeptisisme Profesional Sebagai Variabel Moderasi - Nieke Yunianti; Yenni Carolina; Vincent Tanu Winata (Jurnal Akuntansi, 2021)
Abstract The motivation of this study is to examine and provide evidence regarding the interaction of the independent variable (X1) and auditor's work experience (X2) with the audit quality variable (Y) and the interaction of the professional skepticism variable (Z) as a moderator variable in strengthening the interaction of X1 and X2 with variables Y. The research is focused on active Public Accountants (partner auditors) who are licensed and registered with IAPI. The results of distributing questionnaires to Public Accountants obtained 309 questionnaire sample data. The Slovin technique was used in the data collection technique, while the data analysis used the SEM PLS (Structural Equation Modeling-Partial Least Square) method. This study provides evidence that 1) auditor independence has a positive effect on audit quality, 2) auditor's work experience has a positive effect on audit quality, 3) auditor's professional skepticism has an effect on strengthening the relationship between auditor independence and audit quality, and 4) auditor's professional skepticism has an effect on strengthen the relationship between auditor work experience and audit quality. Keywords: Audit Quality, Independence, Work Experience, and Professional Skepticism